The Effect of Corporate Governance and Ownership Structure on Financial Performance of Listed Companies in Nepal (Journal of Nepalese Business Studies, 2019)
The paper attempts to analyze relationships among corporate governance, ownership structure and firm performance in Nepal. The study comprises of panel data set of 25 firms listed at Nepal Stock Exchange (NEPSE) covering a period of five years from 2012 to 2016. The econometric methodology for the study consists primarily of least squares dummy variable (LSDV) model, fixed and random effects panel data models and two-stage least squares (2SLS) model. The study finds bi-directional relationship between corporate governance and performance. Among corporate governance internal mechanisms; smaller board size, higher proportion of independent directors, reducing ownership concentration, improving standards of transparency and disclosure, and designing appropriate director compensation package are important dimensions that listed firms and regulators in Nepal should focus on. Ownership concentration is found to have positive effect on performance; however, it affects corporate governance negatively. This study raises understanding and provides empirical evidence for endogenous relationship between corporate governance and performance and offers support for principal-principal agency relationship. The results of this study lead to several practical implications for listed firms as well as policymakers of Nepal in promoting sound corporate governance practices and codes. For listed companies, the improvement in compliance with a code of corporate governance or voluntary adoption of best practices can provide a means of achieving improved performance.